Liver-specific overexpression of matrix metalloproteinase 9 (MMP-9) in transgenic mice accelerates development of hepatocellular carcinoma - Thieringer, Florian Rolf; Schirmacher, Peter; Longerich, Thomas (Molecular carcinogenesis, 2012)
Matrix metalloproteinase-9 (MMP-9) plays a central role in tumor invasion and development of metastases. Expression of MMP-9 had been shown in human hepatocellular carcinomas (HCCs). However, it remained unclear whether MMP-9 could influence development of HCC. In order to address this issue, we generated transgenic mice overexpressing MMP-9 in the liver. In order to avoid embryonic lethality a Cre-lox system was utilized for conditional overexpression of MMP-9 under control of an albumin enhancer and promoter. Induction of MMP-9 overexpression in transgenic mice was achieved by i.v. injection of an adenovirus coding for the Cre recombinase. Initiation of liver carcinogenesis was achieved by injection of diethylnitrosamine (DEN) followed by Phenobarbital administration in drinking water. Transgene expression was induced at the age of 6?wk. Four and six months later mice were sacrificed and examined macroscopically and microscopically in a blinded manner. Alb/Cre/MMP-9-transgenic mice showed liver specific overexpression of MMP-9-mRNA and protein after induction. At the age of 6 months livers of transgenic mice showed 15.7 +/- 11.6 tumors (mean +/- SD) in contrast to wildtype mice with only 7.9 +/- 11.0 tumors (P?<?0.03). By histopathology examination of the livers HCCs were identified in 42% of the transgenic mouse livers but only 8% in wildtype animals. In summary, we established a novel MMP-9 transgenic mouse model, and report on a significantly increased susceptibility of MMP-9 transgenic mice to chemically induced carcinogenesis. This is the first in vivo proof that MMP-9 overexpression promotes liver tumor development.
Gesehen am 24.04.2018
Article was published online on 16 June 2011